Penerapan Algoritma ELECTRE pada Pemilihan Cream Pelembab Berdasarkan Konsumen - Agus Perdana Windarto; Wida Prima Mustika (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
The aim of the study is to recommend the selection of a moisturizing cream using a decision support system ranking technique seen from consumer ratings. This research was conducted in the city of Pematangsiantar. Data obtained by observation to several stores to ensure the availability of moisturizing cream, interviews and observations to 250 consumers who were randomly conducted when they made a transaction to purchase a moisturizing cream. In this case, this research needs to be done considering that moisturizer is a drug used to make facial skin feel moist because with skin that feels moist will make women avoid various problems such as blackheads and acne. Keeping facial skin moist and oil free is not an easy thing for users to do. In addition, the number of moisturizing cream products that are currently making many women confused in choosing a moisturizing cream. Therefore researchers used a Decision Support System (SPK) with the ELECTRE algorithm in recommending the selection of a moisturizing cream based on consumer ratings. In this case the researchers used several assessment criteria including: product price (C1), side effects of usage (C2), product quality (C3), customer commitment (C4), customer trust (C5) and usage reaction (C6). While the alternatives used include: Citra Hazeline (A1), Fair & Lovely (A2), Garnier (A3), Olay (A4), Sariayu (A5) and Wardah (A6). The results of the assessment using the ELECTRE method are Fair & Lovely (A2) and Wardah (A6) as the best moisturizing cream recommendations based on consumer choice